2016
DOI: 10.3390/ma9120972
|View full text |Cite
|
Sign up to set email alerts
|

Admixtures in Cement-Matrix Composites for Mechanical Reinforcement, Sustainability, and Smart Features

Abstract: For more than a century, several inclusions have been mixed with Portland cement—nowadays the most-consumed construction material worldwide—to improve both the strength and durability required for construction. The present paper describes the different families of inclusions that can be combined with cement matrix and reviews the achievements reported to date regarding mechanical performance, as well as two other innovative functionalities of growing importance: reducing the high carbon footprint of Portland c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 156 publications
0
10
0
Order By: Relevance
“…This is because pozzolanic activity of TiO 2 in hydrating cement attributed to the improvement of compressive strength of the modified concrete. There is a research on the effect of nanomaterials as cement replacement on physical properties of concrete, reported that the compressive strength of concrete and cement by using various nano products that commonly used in published research as additives and admixtures was reduced as in Table 1 [17].…”
Section: Mechanical Properties On Self-cleaning Concretementioning
confidence: 99%
“…This is because pozzolanic activity of TiO 2 in hydrating cement attributed to the improvement of compressive strength of the modified concrete. There is a research on the effect of nanomaterials as cement replacement on physical properties of concrete, reported that the compressive strength of concrete and cement by using various nano products that commonly used in published research as additives and admixtures was reduced as in Table 1 [17].…”
Section: Mechanical Properties On Self-cleaning Concretementioning
confidence: 99%
“…The COMSTAT analysis of the confocal images was well in agreement with the quantified results (Tables and ). In addition to the antibacterial activity, nanoparticles also act as fillers whereas, nitrite ions are reported to have good antimicrobial activity , thereby increasing the degradation resistance of CFNI specimens.…”
Section: Discussionmentioning
confidence: 99%
“…For further clarification, many admixtures are added to the concrete mixture along with basic components (cement, water, aggregates) which can be added during the mixing process of the basic components in order to improve the properties of the concrete mixture. The improved properties vary according to the type of the admixture, where there are admixtures that improve the workability of the concrete and its durability, or accelerate or slow the cohesion of concrete, another admixture type works on increasing the wear resistance of the concrete surface, and there are admixtures minimizing the amount of water needed,K..etc [22,23]. Oxydtron contains high-temperature oxides and carbonates that make it one of the alternative options for conventional flame retardants used today [20].…”
Section: Introductionmentioning
confidence: 99%